High dosage of Prostate-Specific Antigen (PSA) in a patient after radical prostatectomy and without clinical evidence to support tumor recurrence: case report (Research, Society and Development, 2021)
Introduction: in the clinical evaluation of the prostate, during the digital rectal examination, irregular nodules in the external glands located in the periphery of this organ can be recognized. Among the types of existing pathologies, prostate adenocarcinoma is the most common neoplasm of this tissue, as well as the second with the highest incidence in males in Brazil. Objective: to demonstrate a clinical case of high dosage of Prostate Specific Antigen (PSA) in a patient after radical prostatectomy and without clinical evidence that attest to tumor recurrence. Methodology: this is a clinical case study with a qualitative and descriptive perspective, which consists of a research that, in general, takes place with direct data collection, in which the researcher is the indispensable instrument. Case report: This is a patient diagnosed with prostate adenocarcinoma and undergoing radical prostatectomy. Even after surgical removal, the PSA dosage remained high, however, without any clinical findings attesting to a possible tumor recurrence. Discussion: PSA, despite being widely used as a complement to the diagnosis of prostate cancer, is also used during follow-up and verification of therapeutic efficacy. Thus, it is noteworthy that the increase in the values ​​of this marker after radical prostatectomy, configuring a biochemical recurrence, is not always an indication of metastatic processes or tumor recurrence. Conclusion: in this case, it is imperative that complementary tests, such as bone scintigraphy and magnetic resonance, are performed to absolutely rule out diagnoses indicative of malignancy and to indicate the proper management of the clinical picture. Under this bias, after an individualized assessment, an acceptable alternative is the introduction of hormone therapy to stabilize these still high PSA values.